Repeated sevoflurane exposure causes hypomyelination in the prefrontal cortex of adult male mice - Linyong Zhang; Zhidan Ke; Ning Zhang; Dechuan Wang; Liang Zhou (Scientific Reports)
Abstract As one of the most commonly used general anesthetics (GAs) in surgery, numerous studies have demonstrated the detrimental effects of sevoflurane exposure on myelination in the developing and elderly brain. However, the impact of sevoflurane exposure on intact myelin structure in the adult brain is barely discovered. Here, we show that repeated sevoflurane exposure, but not single exposure, causes hypomyelination and abnormal ultrastructure of myelin sheath in the prefrontal cortex (PFC) of adult male mice, which is considered as a critical brain region for general anesthesia mediated consciousness change. Furthermore, disrupted proliferation of oligodendrocyte precursor cells (OPCs) contributes to repeated sevoflurane exposure-induced myelin defect. This may be owing to an accumulated tuberous sclerosis complex 1 (TSC1) expression and inhibition of mammalian target of rapamycin (mTOR) signaling, leading to the unbalance of TSC1-mTORC1 activity after repeated sevoflurane exposure, which is critical for proper myelination of the central nervous system (CNS). Moreover, repeated sevoflurane exposure aggregates myelination defect in the cuprizone-induced demyelination model. Together, our present work establishes the role of sevoflurane exposure in myelin integrity in the PFC of the adult male mice and provides a new insight to elucidate the mechanism of GAs-induced brain dysfunctions.